2014
DOI: 10.7314/apjcp.2014.15.22.9847
|View full text |Cite
|
Sign up to set email alerts
|

Decreased HDL-Dependent Paraoxonase and Arylesterase Enzyme Activity May Indicate a Worse Prognosis in Multiple Myeloma

Abstract: Background: Multiple myeloma (MM) is a haematological cancer characterized by clonal proliferation of plasma cells.The aim of this study was to investigate the activity of serum paraoxonase-1 (PON1) and arylesterase (ARE) in multiple myeloma with and without free light chain excretion(FLCe-MM and NFLCe-MM); as well as to investigate possible alterations in oxidative stress parameters. Materials and Methods: Total thiol (T.thl), oxidative stress index (OSI), total oxidant status (TOS) and total antioxidant stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…On the other hand, it has been recently ac knowledged that HDL functionality is more critical than its concentration [19,42,43]. PON1 and ARE, which are important indicators of HDL function, are multifunctional enzymes that have antioxidant, antiatherogenic, lactonase and homocysteinethio lactonase activities [44,45]. In our smaller group of 100 individuals, although there was a negative correlation between HDLC and SFer levels, there was no correlation between SFer levels and PON1 or ARE activities.…”
Section: Parameterscontrasting
confidence: 49%
“…On the other hand, it has been recently ac knowledged that HDL functionality is more critical than its concentration [19,42,43]. PON1 and ARE, which are important indicators of HDL function, are multifunctional enzymes that have antioxidant, antiatherogenic, lactonase and homocysteinethio lactonase activities [44,45]. In our smaller group of 100 individuals, although there was a negative correlation between HDLC and SFer levels, there was no correlation between SFer levels and PON1 or ARE activities.…”
Section: Parameterscontrasting
confidence: 49%
“…Notably, in the stratified analysis by ethnicity, a significantly reduced risk of the overall cancers under allele contrast model was uncovered in Caucasian. Previous studies indicated that PON1 192 Q allele carriers were reported to be lower than that of the R carriers (Davies et al, 1996;Mackness et al, 1997;Li et al, 2000), and a lower PON1 level was regarded as a risk for cancer (Ellidag et al, 2014); notably, allele distributions varied obviously in control groups when stratified by the ethnic group, a result consistent with those reported by the National Center of Biotechnology Information (NCBI) for Caucasian (Q: 0.668) and Asian population (Q: 0.430).…”
Section: Discussionsupporting
confidence: 81%
“…An 8-OHdG provides a useful indicator and reliable approach for the assessment of oxidative DNA damage in vivo. Elevated oxidative DNA damage in patients with MM cancer may be associated with previous studies, which have indicated the decrease in enzymatic and non-enzymatic antioxidant system as well as increase in free radicals or reactive metabolites in MM patients (24)(25)(26)(27). Nitrite and nitrate are both eventual fates of nitric oxide (NO) oxidation, known as end-products of endogenous NO metabolism.…”
Section: Discussionmentioning
confidence: 99%